The role of the European Union in climate negotiations after the Paris Agreement (Revista de Estudios Europeos, 2026)
Since the creation of the United Nations Framework Convention on Climate Change in 1992, the European Union has played a significant role in the international climate negotiations. The European proposals and the climate commitments assumed have been among the most ambitious approaches. Therefore, it is often stated that the European Union is a leader in international climate action. This text describes and analyses the role of the European Union in the international climate negotiations to implement the Paris Agreement. The objective of the study is to determine the extent to which the European Union is leading climate action.
Keywords: European Union; climate action; Paris Agreement; emissions reduction; shared leadership